Successful use of the Gellhorn pessary as a second-line pessary in women with advanced pelvic organ prolapse. Issue 11 (November 2017) - Deng, Mou; Ding, Jing; Ai, Fangfang; Zhu, Lan
Abstract: Objective: The primary outcome of this study was the efficacy of the Gellhorn pessary in patients with advanced pelvic organ prolapse (POP) who failed to retain a ring with support pessary, and the secondary outcome is the related factors that influence its successful use. Methods: Between May 2015 and May 2016, women with POP quantification stage III to IV, who initially failed to place a ring with a support pessary, but were then successfully fitted with a Gellhorn pessary, were included. We performed independent-sample t tests, nonparametric tests, chi-square tests, and logistic regressions for data analysis. Results: A total of 82.3% (65/79) participants were successfully fitted with a Gellhorn pessary at the fitting. At 3 months, 46 participants continued to use the pessary, whereas 19 discontinued use, indicating a success rate of 70.8% (46/65). All the participants were satisfied with their pessary. More than half experienced mild complications such as vaginal erosion or discharge. The presence of predominant prolapse in the anterior wall may be an influential factor for successful pessary use ( P < 0.01), whereas a higher body mass index or a history of prior hysterectomy or prolapse surgery was associated with discontinuation. Conclusion: For patients with advanced POP who failed to retain a ring with support pessary, the Gellhorn pessary can be offered as a second option. Body mass index, the presence of predominant anterior wall prolapse, and a previous hysterectomy or prolapse surgery may be potential factors influencing the outcomes of Gellhorn pessary use.